Pendekatan Kearifan Lokal Masyarakat Dalam Mitigasi Bencana Abrasi Pantai di Kecamatan Galesong Utara Kabupaten Takalar - Firdaus; Multazam Mustadjab; Diva Auliya Yuniar; Ayu Ariani (Formosa Journal of Sustainable Research, 2022)
Local wisdom has a good way to preserve the environment that has not been the focus of disaster mitigation, especially in coastal areas. The purpose of this study was to determine the approach of local community wisdom in mitigating coastal abrasion in North Galesong District, Takalar Regency. This research method uses a qualitative descriptive analysis method based on the results of field observations and interviews with communities affected by abrasion. Local wisdom approaches in mitigating coastal abrasion disasters in the long term are Appanaung Rije'ne, Siri' na Pacce Festival, Mappalette Bola, Kasipalli and Appadekko so that the community is involved and aware of the dangers of disasters that will occur. Local wisdom of the community needs to be the main capital in building the civilization of a city and region that is more resilient in the face of natural disasters